Factors that explain loyalty towards an online trading company in Mexico, in times of health crisis (Revista de Investigaciones Universidad del Quindío, 2021)
Currently, companies are innovating the way in which they offer their products and services making use of the wide range of existing technologies, with digital platforms gaining more relevance. That is why customer loyalty is one of the most relevant analysis elements within digital platforms due to the easy change of preference. For this reason, this research validated a model, using the technique of modeling structural equations to verify the influence that the variables usability of the platform, satisfaction and customer trust have on loyalty towards the electronic commerce platform in Mexico. The research is quantitative, transversal and explanatory. The analysis of the results was carried out with information provided by 350 users of a digital commerce platform and by obtaining a model that met the requirements of convergent and discriminant validity, and with a reasonable level of adjustment, it was found that the variables Consumer satisfaction and trust have a positive and significant influence on the platform's consumer loyalty, while the platform usability variable did not experience statistical significance.
Keywords: company loyalty; usability; satisfaction; trust; SEM